The Role of E-Money in Sustainable Smart City Development in Bogor City Area - Gustian Rama Putra; Wahyu Sardjono; Oktavian Nursetiaji; Agita Tiara Putri; Asep Saepulrohman; I Wayan Sriyasa (Ilmu Komputer, FMIPA, Universitas Pakuan, 2022)
In the current era of society 5.0, especially in industry 4.0, the use of information systems is very important where in this era the community is expected to help the development of smart cities. In this era, people always carry out activities with technology and digitalization, one of which is how to transact that transforms electronically with technology. Currently, e-money is considered to have its own role in the sustainability of community activities, especially in the city of Bogor, so that if the role of e-money can be utilized, a positive value can be generated for the sustainability of smart city development. To assess the success of the role of e-money, this research instrument was built using the DeLone and McLean methods in building a research model that aims to support the development of smart cities with aspects of indicators such as information quality, system quality, service quality, user satisfaction level, utilizing and net benefit. The research method used in this study is factor analysis to process the data obtained from the questionnaire. The Alpha Cronbach value in this study has a value of 0.971 or 97.1%, so it can be concluded that the positive influence of e-money is very large to support the development of smart cities in Bogor City. This research is expected to provide information related to the sustainable development of smart cities in Bogor City.